Regeneration of informal areas: An integrated approach. (October 2016) - Amado, Miguel P.; Ramalhete, Inês; Amado, António R.; Freitas, João C.
Abstract: Living conditions in informal areas present a severe problem to the development of society, particularly to public health and the respective socioeconomic context. People in these areas have no viable alternative to solve this problem themselves. In this study, several successful approaches are surveyed and new methods are developed to design a holistic process capable of not only tackling the issue of informal settlements, but doing so in a way that is cognizant of the current global economic reality and that integrates all the dimensions of sustainable development. In this study, an integrated regeneration strategy for Luanda's metropolitan plan in Angola is developed. The methodology is supported by a social context analysis and highly participative design process. The informal settlements vary in type and structure, urban patterns, and their social and economic structure. These factors have been taken into consideration in the approach advanced in this study, as they are deemed key aspects for the fine-tuning of the final approach. Hence, a partnership model is presented, where the public sector provides development conditions for the private sector. The model is supported by regeneration mechanisms that establish the roles and procedures of each stakeholder within the process. Multiple criteria for rehousing as well as guidelines for social and affordable housing are used to create an integrated approach. Highlights: Literature on regeneration at urban level is reviewed. New methods to design a holistic process of urban regeneration are presented. The process based on the interplay between public and private sectors is discussed. A set of mechanisms is created to transform informal settlements into more resilient settlements. The methodology for regeneration of informal urban areas is described.